Intravesical delivery of mucoadhesive and tumor-selective-penetrating nanozymes for enhancing the PDT of bladder cancer - Yang Liu; Wentao Xu; Xiaowen Qin; Jiajia Zheng; Bin Zheng; Li Sun; Wenyan Zuo; Dingyi Liu; Zhenghong Liu; Yixuan Mou; Heng Wang; Qi Zhang; et al. (Journal of Nanobiotechnology)
Abstract Intravesical photodynamic therapy (PDT) emerges as a promising modality for bladder cancer treatment, yet its efficacy is often curtailed by weak muco-adhesion, poor muco-penetration, low tumor-targeting and intra-tumoral oxygen scarcity. In this work, we introduce a drug delivery system leveraging cerium oxide (CeO2) nanozymes as the core, polyarginine peptides R11 as the tumor-targeting ligands, and indocyanine green (ICG) as the photosensitizers, with the latter two components assembled on the particle surface. Intravesical ICG@R11-CeO2 nanoparticles displayed enhanced mucoadhesive, mucus-penetrating and tumor-targeting properties, and effectively mitigated the hypoxia threat in the tumor microenvironment to improve the PDT sensitivity. Remarkably, the intravesical PDT via ICG@R11-CeO2 nanoparticles achieved complete tumor inhibition in orthotopic bladder cancer models, offering strong evidence on its clinical translational potential.